Adenosquamous Cell Carcinoma of the Stomach 18F-FDG PET/CT Diagnosis and Review of Literature - Darouichi, M; Jovanovic, S; Constanthin, P (Journal of Digestive Disorders And Diagnosis, 2016)
Adenosquamous carcinoma of the stomach (ASCS) is extremely rare with less than one hundred cases published in the world literature. It is defined by combined adenocarcima and squamous cells carcinoma of the stomach. ASCS is clinically aggressive and has a poor prognosis, even when discovered at an early stage. This intriguing entity is characterized by non specific symptoms or radiological signs. Integrate 18F-fluorodeoxyglucose positron emission tomography/computed tomography 18F FDG.PET/CT is useful morphologic and functional modalities for evaluating primary tumor, local extend and invasion beyond gastric wall or distant metastatic and eventually for management. Diagnosis of ASCS requires immunohistochemical confirmation. We report a 77-year-old man who was admitted to hospital because of epigastric pain, vomiting and melena since more than a month. Gastroscopy with biopsies had initially suggested gastric squamous cell carcinoma .Thoracic and abdominal computed tomography scan (CT) showed a huge mass in the gastric body, largely necrotic, infiltrating the adjacent structures without metastases. Partial gastrectomy with resection of the proximal 2/3 of the stomach, the spleen, the body and tail of pancreas and the left transverse colon was performed. Immunohistochemical analysis demonstrated ASCS with mixed adenocarcinomatous and squamous cells carcinoma with invasion of gastric lymph nodes. Unfortunately, two months after surgery, a CT of the abdomen revealed diffuse metastasis and the patient died three months later. In light of this case, we discuss the pathogenesis, staging and monitoring of this rare entity by combined 18F-FDG PET/CT with review of the literature.
Keywords: adenocarcinoma; squamous cell carcinoma; Stomach; pathogenesis; (18)F-FDG.PET/CT; immunohistochemical.